Efektivitas Model SQ4R Berbantuan Kartu Cakap Terhadap Keterampilan Membaca Pemahaman Teks Eksplanasi Peserta Didik - Lestari, Fitriana Ayu; Heryanto, Dwi; Rahmawati, Evi (Jurnal Didaktika Pendidikan Dasar, 2025)
This research was motivated by the low reading comprehension skills of fifth-grade elementary school students in Phase C in Indonesian language, specifically in explanatory texts. The purpose of this research was to determine the effectiveness of the SQ4R learning model assisted by CAKAP cards in improving students’ reading comprehension skills in this subject matter. This study used a quantitative approach with a pre-experimental method, a one-group pretest-posttest design, involving 24 students at an elementary school in Bandung Regency. The instruments were written tests in the form of multiple-choice and essay questions, with data analysis through normality tests, hypothesis tests, and N-Gain score difference tests. The results showed an average increase from 48.96 (pretest) to 76.79 (posttest). The hypothesis test obtained a significance of 0.001 < 0.05, so H0 was rejected and H1 was accepted. This means that there was a significant increase in reading comprehension skills, while the N-Gain score of 0.5720 (moderate) with a percentage of 57.1997% proves that the SQ4R model assisted by CAKAP cards is quite effective in improving the reading comprehension skills of explanatory texts in Phase C elementary school students.